Antibiotic Susceptibility Pattern and Biofilm Formation in Clinical Isolates of Enterococcus spp. - Shridhar, Sridevi; Dhanashree, Biranthabail (Interdisciplinary Perspectives on Infectious Diseases, 2019)
Enterococcus is a commensal in the intestine and is now emerging as a drug-resistant pathogen. It produces different virulence factors. Enterococcus surface protein (esp) is a virulence factor that helps in the adhesion, but its role in biofilm formation is still contradictory. Moreover, in many bacterial species, strong biofilm producer exhibits multidrug resistance. Hence, this study is done to know the antimicrobial susceptibility pattern of Enterococcus spp. and to correlate the drug resistance with biofilm production and esp gene. Enterococcal isolates were collected from various clinical specimens. Antibiotic susceptibility testing was done by disc diffusion, and biofilm production was performed by microtiter plate method. PCR was performed for detection of esp gene. Two E. faecium strains resistant to vancomycin and high-level aminoglycoside (HLAR) were non-biofilm-producers and did not harbor esp gene. However, other biofilm-producing E. faecium harbored esp gene, and this association was found to be statistically significant (p=0.024). It was observed that there was no significant association between biofilm formation and presence of esp gene in E. faecalis. Moreover, a significant correlation was not found between drug resistance and biofilm production in both Enterococcus species. Thus, biofilm formation is not always associated with the presence or absence of esp gene and or drug resistance in Enterococcus spp.